APLIKASI MOBILE LEARNING ILMU BIOLOGI UNTUK SISWA KELAS X SEKOLAH MENENGAH ATAS BERBASIS ANDROID (Studi Kasus SMA N 10 Padang) - Liranti Rahmelina; Legiman Slamet; Yasdinul Huda (Universitas Negeri Padang, 2014)
The background of this research background by the development of smartphones and mobile technology or operating system on smartphones, such as Android. This research aims to produce a system design for mobile learning Biology class X, Th Semester. 2013/2014 teachings in SMA N 10 Padang, preferably in the learning process in biology, the nature of the book memorization. Besides, the lack of media used can sometimes make children often get bored in studying biology. This study was designed with the software modeling language with object-oriented programming method that uses modeling languages ​​Unified Modeling Language (UML). The programming language used is Java, using the Eclipse IDE. Trials will be conducted on the 2.2 emulator. while the implementation is done at the Samsung Galai Young with Android 4.0.1. In general, the results are displayed on the emulator and Galai Young is not much different, it's just Android with a higher version has faster access speed. Keywords : Mobile Learning, Biological Sciences High School Class X, Android Application.